GE_GERICHTE C/26135/2013 vom 22. Mai 2015 - GE Cour de justice (2015)
MAINLEVÉE DÉFINITIVE; TITRE DE MAINLEVÉE; DÉCISION ÉTRANGÈRE; COURS DE CONVERSION; ERREUR; TAUX D'INTÉRÊT | LP.80.1; LP.281.2; CL.33.1; LP.67.3